ChemInform Abstract: An Efficient and Convenient Method for Synthesizing New Derivatives of Pyrido[2, 3‐e]pyrrolo[1, 2‐a][1, 4]diazepine‐5, 10‐dione via Sonogashira, Suzuki—Miyaura, and Stille Cross‐Coupling Reactions. Issue 12 (14th March 2013) - El Bouakher, Abderrahman; Prie, Gildas; Aadil, Mina; Lazar, Said; El Hakmaoui, Ahmed; Akssira, Mohamed; Viaud‐Massuard, Marie‐Claude
Abstract The chiral diazepine dione derivative (III) is used as starting material for the synthesis of a variety of 3‐substituted derivatives, which represent bioisosteres of the anthramycin scaffold.